2021
DOI: 10.3389/fcell.2021.672862
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Subcellular and Ultrastructural Changes During Vitrification of Human Spermatozoa: Effect of a Mitochondria-Targeted Antioxidant and a Permeable Cryoprotectant

Abstract: Mitochondria-targeted antioxidants have great potential to counterbalance the generated reactive oxygen species (ROS) because they cross the inner membrane of the mitochondria. Still, their use was not reported in vitrified human spermatozoa. Our laboratory has successfully vitrified spermatozoa without the use of permeable cryoprotectants, but subcellular-level evidence was missing. Therefore, this study aimed to improve spermatozoa vitrification using a mitochondria-targeted antioxidant (mitoquinone, MitoQ),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 95 publications
(119 reference statements)
9
21
0
Order By: Relevance
“…However, some recent literature indicates that mature spermatozoa can use mitochondrial RNA transcripts for protein translation during the final maturation steps before fertilization [ 13 , 14 ]. In our previous study, we found that some proteins are altered, resulting in higher or lower expression levels of proteins in spermatozoa subjected to vitrification; due to proteomic study only, we can propose that some functional proteins are not altered/modified that were reported to be altered in most of the conventional slow freezing method studies [ 15 ]. Like our studies, the increased or decreased alteration of some proteins in cryopreserved spermatozoa has been reported in some studies [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some recent literature indicates that mature spermatozoa can use mitochondrial RNA transcripts for protein translation during the final maturation steps before fertilization [ 13 , 14 ]. In our previous study, we found that some proteins are altered, resulting in higher or lower expression levels of proteins in spermatozoa subjected to vitrification; due to proteomic study only, we can propose that some functional proteins are not altered/modified that were reported to be altered in most of the conventional slow freezing method studies [ 15 ]. Like our studies, the increased or decreased alteration of some proteins in cryopreserved spermatozoa has been reported in some studies [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed significantly lower sperm viability and motility in the vitrified groups than in the fresh control group, which is in agreement with earlier studies [ 29 - 31 ]. Cryopreservation has deleterious effects on sperm motility by damaging the plasma membrane and mitochondrial function [ 29 , 32 ]. However, we did not find statistically significant differences in the viability and motility parameters of post-thawed samples between sucrose vitrification and the commercial sperm freezing medium.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with other research on human sperm cryoinjury [ 39 ], which indicated that the extracellular ROS levels increased during cryopreservation by increasing mitochondrial and membrane NADPH oxidase-5 (NOX5) activity. The increased ROS production following cryopreservation may be a result of mechanical damage to the sperm plasma membrane [ 32 , 40 ]. An alternative explanation is that the balance between ROS production and antioxidant scavenging systems is disrupted during the freezing-thawing process.…”
Section: Discussionmentioning
confidence: 99%
“…Cryopreservation involves sudden osmotic and temperature changes that may lead to molecular disturbances in the sperm transcriptome and proteomics [7][8][9]. A thorough understanding of these molecular disorders during cryopreservation is essential in order to optimize current cryopreservation protocols [2].…”
Section: Introductionmentioning
confidence: 99%